Clinical and Histopathologic Characterization of Canine Chronic Ulcerative Stomatitis. (May 2017) - Anderson, J. G.; Peralta, S.; Kol, A.; Kass, P. H.; Murphy, B.
Canine chronic ulcerative stomatitis, also known as chronic ulcerative paradental stomatitis, is a painful condition of the oral cavity. The purpose of this study was to determine if there are commonalities in clinical and radiographic features among patients, whether the histopathologic evaluation might inform the pathogenesis, and whether the condition appears similar to human oral mucosal diseases. To do this, we prospectively collected clinical, radiographic, and histopathologic data from 20 dogs diagnosed with the disease. Clinical data were based on a clinical disease activity index, oral and periodontal examination parameters, and full-mouth dental radiographs. The histopathological and immunohistochemical data were based on oral mucosal samples obtained from erosive or ulcerated areas. Our findings revealed that canine chronic stomatitis is clinically characterized by painful oral mucosal ulcers of varying size, pattern, appearance, and distribution, most often associated with teeth with early periodontitis. Histologic examination revealed a subepithelial lichenoid band (interface mucositis) where B cells, T cells, and Forkhead-box protein 3 (FoxP3)– and interleukin-17–expressing cells were present. These cells might play a role in the underlying immune response and an immune-mediated pathogenesis is suspected. The clinical and histopathologic features of this chronic inflammatory mucosal disease in dogs resemble those of oral lichen planus in humans.